(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Experiential marketing helps make a memorable experience for the consumer. Consumer characteristics enable them to perceive the offered stimuli differently. This study investigates the differences in the evaluation of artscapes – the application of servicescape in the performing arts – according to opera attendees’ experience with the cultural organization. Literature framework fails to confirm differences between experienced and inexperienced visitors. However, the level of commitment with the artistic organization contributes to building a deeper relationship. On the basis of 867 Spanish opera attendees’ responses, a one-way ANOVA technique has been used to analyze the proposed hypotheses, adopting a holistic perspective of the artscape, which includes not only its tangible, physical dimensions but also the social ones. Significantly different evaluations of the artscape show that the attendees’ experience is important as the basis for adequate segmentation. The greater the extent of the contractual relationship and contact with the opera house, the better the evaluation of the physical and social artscape. This paper helps to fill a research gap in the area of servicescape applications in the nonprofit performing arts. In addition, it provides deeper knowledge about the servicescape experience.